Problematika Guru Dalam Peningkatan Kompetensi Di SD Negeri 1 Simo - Zulaikah, Isma; , Minsih. S.Ag, M.Pd (2017)
ABSTRACT Teacher is the most important component in education. So that, to a achieve a purpose in education, teacher must have one of the requirements of education, that is about competency. The standards of competency as a requirements in education are pedagogy competence, professional competence, personal competence, and social competence. This research aim to describe: 1) the kinds of teacher's problem in improving competency, 2) the obstacles' teacher in improving competency, 3) the efforts to solve the problems in improving the teacher's competency. The kind of this research is qualitative research with fenomenology desain. Informan in this research are the headmaster and the teachers of SD Negeri 1 Simo. The data collection technique in this research are interview, observation, and documentation. Investigation technique of data validity is done by triangulation techniques and triangulation of sources. The data was analyzed through four step, such as data collection, data reduction, data presentation, and collecting conclusion. The result of this research indicate the kinds of teacher's problem in 1) improving competency, such as composing the Lessons Plan which inappropriate with the dealing time, the less of teacher's interest in research, the teacher's achievement about profession's rules, and the lack of communication between teacher and society. 2) based on the kinds of those problem was caused of the constraints such as; limiting time in teacher, motivation in research, and less skill of teacher. 3) from the teacher and headmaster has try to cope the variety of the problems such as making the best use of time and join the research. Keywords: Competency, Profession's rules, Problems